Alternativa de compostaje sostenible con los residuos vegetales generados del mantenimiento en las áreas verdes del humedal la vaca. - Casas Pérez, Jennyfer Lizeth (Universidad Antonio Nariño, 2021)
This project was inspired by the need to properly compost waste vegetables from the maintenance of the La Vaca Wetland, located in UPZ 80 called Cora bastos in the town of Kennedy. This wetland currently performs composting in a very artisanal way negatively impacting the environment with the activities of proliferation of vectors in the area, use of chemical products to control odors among other